A SWOT Analysis of Early Childhood Educational Institutions in Thailand: Insights for Chinese Immigrant Families - Liu, Danni; Arifani, Yudhi (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study employs a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to evaluate the adaptability of Thailand’s early childhood education (ECE) institutions in addressing the needs of Chinese immigrant families. Using mixed-methods research, including surveys of 278 families and qualitative interviews, the analysis identifies systemic strengths, such as bilingual programs and cultural inclusivity, alongside critical weaknesses, such as inconsistent educational quality and socioeconomic disparities. Opportunities for improvement include policy reforms and technology integration, while threats center on cultural misalignment and limited parental engagement. The findings advocate for culturally responsive curricula, enhanced teacher training, and equitable funding models to foster inclusive learning environments. This research contributes to global discussions on immigrant education by highlighting the intersection of cultural adaptation, language acquisition, and institutional policy in Thailand’s ECE landscape.